The Relationship Between the NSP and the Individual and Work Organizational Variables: A Cross-Sectional Study - Yuan, Sue; Li, Yunxia; Zhang, Lihui; Wang, Honghong (Frontiers in Public Health, 2022)
Objectives: To investigate the characteristics of neck–shoulder pain (NSP) and identify the individual and organizational factors associated with NSP. Methods: A cross-sectional study was performed in the tertiary general hospitals in Hunan Province, China between May 2019 and July 2019. A total of 2,030 healthcare workers were enrolled randomly in this study based on a three-stage stratified sampling method. The Neck Disability Index (NDI) was used to measure disability in subjects with neck pain. A self-administered questionnaire was used to assess risk factors related to NSP. The Mann–Whitney U test and the Kruskal–Wallis H test were applied to analyze the prevalence of pain intensity among groups. Multivariate linear regression analysis was performed to explore factors related to NSP using the NDI score as the dependent variable, and potential individual and organizational factors related to NSP as the independent variables. Results: 2,008 of 2,030 healthcare workers filled out the survey questionnaires online. In the past 12 months, 1,489 participants (74.2%) complained of pain in the cervical–shoulder region. NDI score increased by 0.10 for each year of age, with healthcare workers working in Obstetrics and Gynecology, and the Operating Room less likely to have NSP than those working in other departments. In contrast, female healthcare workers with a history of pregnancy were more likely to have NSP. In terms of organizational factors, workers who received concern from their supervisor about their health, who had the choice to change their shift status to off duty when they were not feeling well, or who were informed about WMSDs were less likely to have NSP. Conclusion: The prevalence of NSP within the previous year was high in this population. Individual factors including history of neck–shoulder diseases, age, and history of pregnancy and organizational factors including being adequately informed regarding WMSDs, concern from supervisors about workers’ health, and the ability of workers to change their shift status to off duty when they were not feeling well were shown to induce significant effects to NSP.